The effect of short-term fine particulate matter exposure on glucose homeostasis: A panel study in healthy adults. (1st January 2022) - Peng, Shouxin; Sun, Jinhui; Liu, Feifei; Li, Zhaoyuan; Wu, Chuangxin; Xiang, Hao
Abstract: As an emerging risk factor, long-term exposure to fine particulate matter (PM2.5 ) has been linked to glucose homeostasis in numerous epidemiological researches. However, the acute adverse effects of PM2.5 exposure on glucose homeostasis among healthy population are not well described. The study aims to investigate the short-term association between PM2.5 exposure and glucose homeostasis among the healthy populations. We scheduled 8 repeated physical examinations with venous blood collection every 1–2 weeks from 9 September 2019 to 7 January 2020 in a panel of 70 healthy adults (aged 18–26) in Wuhan, China. We measured the individual hourly PM2.5 concentrations, fasting blood glucose (FBG), insulin (FINS) along HOMA-B and HOMA-IR. The linear mixed-effect model was conducted to evaluate the acute effect of PM2.5 on glucose homeostasis. PM2.5 concentrations range varied from 7.38 to 115.38 μg/m 3, with an average level of 38.34 μg/m 3 . Each 10 μg/m 3 increment in 3-days PM2.5 moving average was associated with a 4.19% increase in FINS (95% CI: 2.35, 6.05), 5.95% increase in HOMA-B (95% CI: 3.66, 8.26), and 3.77% increase in HOMA-IR (95% CI: 1.41, 4.64), respectively. We found the adverse effect on HOMA-IR was greater in the overweight (%Change = 7.98; 95% CI: 3.54, 12.61) than in the normal-weight (%Change = 3.35; 95% CI: 1.34, 5.38). And the lifestyle factors, such as exercise also showed a modification effect on the short-term association between PM2.5 and glucose homeostasis. Conclusively, exposure to PM2.5 for short-term, even within hours, was positively associated with elevated IR status and impaired glucose homeostasis in the healthy population. The result may suggest a plausible biological pathway underlying PM2.5 and metabolic events. Highlights: Short-term exposure to PM2.5 was associated with elevated FINS, HOMA-IR, and HOMA-B. Exposure to particulate matter impairs glucose homeostasis. Physiological and lifestyle factors show a modification of the PM2.5 -induced adverse health effect.